1998
DOI: 10.1152/ajplung.1998.275.2.l283
|View full text |Cite
|
Sign up to set email alerts
|

Garlic prevents hypoxic pulmonary hypertension in rats

Abstract: Hypoxic pulmonary vasoconstriction underlies the development of high-altitude pulmonary edema. Anecdotal observations suggest a beneficial effect of garlic in preventing high-altitude symptoms. To determine whether garlic influences pulmonary vasoconstriction, we assessed the effect of garlic on pulmonary pressures in rats subjected to alveolar hypoxia and on vasoconstriction in isolated pulmonary arterial rings. Garlic gavage (100 mg/kg body wt) for 5 days resulted in complete inhibition of acute hypoxic pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 8 publications
7
43
0
Order By: Relevance
“…NE Krebs: contraction with NE in normal Krebs; NE 0Ca1: first contraction with NE in Ca 2+ -free Krebs; NE 0Ca2: second contraction with NE in Ca 2+ -free Krebs. and the implication of calcium channels (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NE Krebs: contraction with NE in normal Krebs; NE 0Ca1: first contraction with NE in Ca 2+ -free Krebs; NE 0Ca2: second contraction with NE in Ca 2+ -free Krebs. and the implication of calcium channels (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, a controversy exists about its mechanism of action. Several authors have proposed a mechanism of action mediated by the activation of nitric oxide synthase in vascular endothelium (2), but a direct effect on vascular smooth muscle has also been demonstrated, suggesting the occurrence of vasodilatation via smooth muscle cell membrane hyperpolarization and/ or inhibition of the opening of calcium channels (3). Together these observations suggest that garlic might block the development of hypertension associated with atherosclerosis, the principal contributor to myocardial and cerebral infarction.…”
Section: Introductionmentioning
confidence: 97%
“…Fallon et al [31] reported that garlic inhibited acute hypoxic pulmonary vasoconstriction in rats and elicited appreciable dose-dependent vasorelaxation in both endothelium-intact and mechanically endothelium-disrupted pulmonary arterial rings. This implies that it can combine both endothelium-dependent and independent process in its hypotensive property [31] [32].…”
Section: Effects Of Garlic On Cardiovascular and Cerebrovascular Disementioning
confidence: 99%
“…This implies that it can combine both endothelium-dependent and independent process in its hypotensive property [31] [32]. In vitro study by [33] indicated that garlic juice can relax the muscles of aorta, trachea, intestines and isolated rabbit heart.…”
Section: Effects Of Garlic On Cardiovascular and Cerebrovascular Disementioning
confidence: 99%
“…9) Other members of the Allium family (e.g., garlic and onion) have also been used as antihypertensives, antiatherosclerotics, antithrombotics, antihyperlipidemics, and antioxidants. [10][11][12][13][14] Many studies have suggested that these beneficial effects were primarily due to organosulfur compounds (e.g., S-allylcysteine and diallyl disulfide). 15,16) However, there have been few studies on the immunomodulatory effects of the bunching onion.…”
mentioning
confidence: 99%